THE INFLUENCE OF KNOWLEDGE-ORIENTED LEADERSHIP AND UTILIZATION OF DIGITAL ISSUES ON INNOVATION PERFORMANCE IMPLICATIONS FOR ADOPTING METAVERSE TECHNOLOGY IN SERANG REGENCY PRIVATE HIGH SCHOOL - Trisna Mukti, Kiki; Umamah, Yuyun; Hajar, Siti; BR Naibaho, Yunika; Basrowi (Center of Language and Cultural Studies, 2023)
This research is entitled The Influence of Knowledge-Oriented Leadership and the Use of Digital Issues on Innovation Performance Implications on Adopting Metaverse Technology in Serang Regency Private High School. The purpose of this study is to get an overview of knowledge-oriented leadership, issue utilization, innovation performance and adopting metaverse technology, knowing the influence of knowledge-oriented leadership on adopting metaverse technology, knowing the influence of using digital issues on adopting metaverse technology , knowing the influence of knowledge-oriented leadership on innovation performance, knowing the influence of using digital issues on innovation performance, knowing the influence of adopting metaverse technology on innovation performance, knowing knowledge-oriented leadership towards adopting metaverse technology through innovation performance as an intervening variable, and knowing the influence of using digital issues on adopting metaverse technology through innovation performance as an intervening variable at Serang Regency Private High School. The research method used is a quantitative descriptive analysis method with a Structural Equation Modeling (SEM-PLS) model using SmartPLS. Based on the results of the study shows that the influence of knowledge-oriented leadership on adopting metaverse technology is positive and significant and the hypothesis is accepted, the influence of the use of digital issues on adopting metaverse technology is positive and significant and the hypothesis is accepted, the influence of knowledge-oriented leadership on innovation performance is positive and significant and The hypothesis is accepted, the influence of adopting metaverse technology on positive and significant innovation performance and the hypothesis is accepted, the influence of knowledge-oriented leadership on adopting metaverse technology through innovation performance as a positive and significant intervening variable and the hypothesis is accepted, the influence of using digital issues on adopting metaverse technology through innovation performance as a positive and significant intervening variable and the hypothesis is accepted.